New faunistic records of cockroaches (Insecta: Blattodea) from Oman - Ali Al-Jahdhami; Sheikha Al-Shukaili (EntomoBrasilis, 2021)
The knowledge of Blattodea from Oman is still incipient. One species of cockroaches are reported from Oman so far and this indicates the large blank in our knowledge in this order when compared to recorded species from other neighboring countries in the Arabian Peninsula.  Blattodea have been collected at various localities in Sultanate of Oman with different sampling artifacts. The present communication records five species of cockroaches from Oman, namely Blattella biligata (Walker, 1868), Heterogamisca Bey-Bienko, 1950, Pycnoscelus surinamensis (Linnaeus, 1758), Tivia fusca Bohn, 2008 from northern Oman and Neostylopyga rhombifolia (Stoll, 1813) from southern Oman.